HUBUNGAN SIKAP TERHADAP MEDIA SOSIAL DENGAN PARTISIPASI SOSIAL IBU-IBU YASINAN DESA NGEMBUL, KABUPATEN BLITAR - BAROKATUL ASIYAH; Annastasia Ediati (Faculty of Psychology, Diponegoro University, 2017)
This study was conducted to determine the relationship between attitudes toward social media with social participation in Yasinan ladies Ngembul Village, Blitar District. The population in this study amounted to 140 mothers of Yasinan members. The sample of this research is 75 people from Dusun Ngembul and Sumberpandan obtained with incidental sampling. The measuring tool used is the scale of attitude toward social media (α = 0,785) and social participation scale (α = 0,876). Simple regression test showed a positive and significant relationship between attitude toward social media with social participation (rxy = 0,476; p <0,001). The more positive attitudes toward social media then the higher the social participation, and vice versa. Attitudes towards social media affecting 22.6% in social segregation and the rest of 77.4% influenced by other factors not disclosed in this study.